2020
DOI: 10.1007/s00392-020-01769-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated markers of thrombo-inflammatory activation predict outcome in patients with cardiovascular comorbidities and COVID-19 disease: insights from the LEOSS registry

Abstract: Aims SARS-CoV-2 infection is associated with adverse outcomes in patients with cardiovascular disease. Here, we analyzed whether specific biomarkers predict the clinical course of COVID-19 in patients with cardiovascular comorbidities. Methods and results We enrolled 2147 patients with SARS-CoV-2 infection which were included in the Lean European Open Survey on SARS-CoV‑2 (LEOSS)-registry from March to June 2020. Clinical data and laboratory values were collected and compared between patients with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…Our colleagues could show elevated markers of thrombo-inflammatory activation in patients with cardiovascular diseases and their prediction for a worse outcome in the population of the LEOSS registry [ 34 ], reinforcing the benefit of early or even pre-existing anticoagulation in these patients in line with our findings in the same population.…”
Section: Discussionsupporting
confidence: 83%
“…Our colleagues could show elevated markers of thrombo-inflammatory activation in patients with cardiovascular diseases and their prediction for a worse outcome in the population of the LEOSS registry [ 34 ], reinforcing the benefit of early or even pre-existing anticoagulation in these patients in line with our findings in the same population.…”
Section: Discussionsupporting
confidence: 83%
“…With respect to the COVID-19 situation, this is of course an absolutely obvious situation. Thrombo-inflammatory factors which even may become predictive markers for COVID-19 complications have been described by Cremer et al [ 46 ]. Other immune biomarkers, as taken together by Fouladseresht et al [ 47 ] have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study including 288 confirmed COVID-19 patients also demonstrated that CVD with older and higher levels of troponin I (TnI), CRP, and creatinine were more prone to develop into severe or critically severe cases ( 22 ). Moreover, 2147 patients with COVID-19 were enrolled in European, patients with cardiovascular comorbidities displayed markedly higher levels of troponin and CRP, which were markers of myocardial injury and thrombo-inflammatory activation in the uncomplicated phase of COVID-19 ( 23 ). When infected by COVID-19, patients with underlying CVD were more likely to exhibit elevation of troponin T (TnT) levels, which was a high and markedly positive linear correlation with plasma high sensitivity CRP (hs-CRP) level ( 24 ).…”
Section: Crp and Covid-19mentioning
confidence: 99%